Development of portable escherichia coli bacteria detection using resistive graphene-based immunosensor - Md Rosni, Nurliyana (2020)
Escherichia coli (E. coli) bacteria comes from the human and animal faeces. It is hazardous to human health and could cause death when not immediately treated. Therefore, it is crucial to detect E. coli bacteria in water before consuming it. Since many cases of water contaminated E. coli bacteria are in rural areas, a portable E. coli bacteria detector is needed. However, many existing biosensors to detect E. coli bacteria are not portable, while the conventional methods are time-consuming and need specialists to perform the task. In this work, an E. coli bacteria biosensor based on the resistivity method was developed using graphene nanostructure as the sensing layer, since carbon materials such as graphene have been known to have biocompatibility and excellent electrical properties. As a result, the concentration of E. coli bacteria can be measured through the change of conductivity caused by the negative charge produced by the E. coli bacteria’s surface. Anti-E. coli antibodies and a blocking agent were employed on the graphene’s surface for selectivity purposes. Characterisations using FESEM, AFM, Raman spectroscopy and contact angle were successfully conducted to study the properties and to verify the presence of the immunosensing properties on the sensing layer. The full system was developed with a standalone user interface and does not require any alternating current (AC) outlet or personal computer (PC) connection. An Arduino microcontroller was used to operate the new device. The circuit was functionalised to detect resistance change with the help of Wheatstone bridge for device calibration. Results show that resistivity change that can be detected by the device was as low as 0.0426 Ω. For E. coli bacteria detection, the system has a linear relationship between the device reading and the concentration of E. coli bacteria. The conductivity of Graphene increased with the increasing of E. coli bacteria concentration. Finally, the validation of the device was performed by comparing the data obtained from the device with plate culture method. The device was found to detect the concentration of E. coli bacteria selectively with LOD between 145 CFU/ml to 7966 CFU/ml with 104 seconds detection time.